Persepsi Pemirsa tentang Tayangan Infotainment di Televisi Kasus Pemirsa Di Bojong Gede, Bogor - Sukarelawati . (Institut Pertanian Bogor, 2009)
This research purposes to know and study the characteristic and perception of the audiences towards theinfotainment program on television and the relation between them. The research was conducted in PerumahanGaperi, Bojong Gede, since November 2008 until 26 January 2009. The research design uses correlation descriptivesurvey with questioner as a primary instrument data collection. Sampling of this research uses simple randomsampling procedure. The amount samples are 80 citizens of Perumahan Gaperi Bojong Gede. The data wereanalyzed descriptively such as the distribution of frequency and infere ntial analyze uses rank Spearman correlationanalyze and Chi-Square. The results indicate that the characteristic of the audiences, such as sex does not havecorrelation to the information value, and the attractiveness of the program format, the age does not have correlationto the information value, but there has negative correlation to the attractiveness of program format, the audiencesexposure does not have correlation to the information value and the attractiveness of the program format, there haspositive correlation between the audiences frequency watching the program to the information value, but does nothave correlation to the attractiveness of the program format, only the occupation and the past experience of theaudiences have correlation to the information value and the attractiveness of the program format. The infotainmentwas inclined to having negative attention or uneducated from some others, so it was normally if the program wasreviewed by the television producer. The attractiveness of the program format tends having not correlation to theaudiences, according to the result above it should be better if the producer of the television increases the moreinteresting to the program format, such as increasing the consistency and objectivity of the information in order tothe infotainment has a bright value for the audiences.